Achieving the Use of National Employment Work Competency Standards for Training Workers in the Construction Sector in Indonesia - Hotma Sitohang; Zainai Mohamed; Syuhaida Ismail (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The Indonesian National Work Competency Standards (SKKNI) are mandatory state laws that must be used as a guideline for training construction workers to improve their competence in construction projects. However, in implementation, there are still many obstacles to achieving success. Therefore, a study is needed to measure the extent to which competency improvement training, which is outlined based on the SKKNI, has an impact on good human resource quality practices by contractors in Indonesia. The questionnaire survey was distributed to 192 construction workers who had obtained a Skills Certificate (SKT) and were involved in 32 multi-storey building construction projects in Jakarta, Indonesia, where Structural Equation Modeling (SEM) was used for data analysis. It was found that the training indicators for competency improvement were mainly the suitability of training materials and relevant fields of work in accordance with the certificate; close relationship between construction workers and management, development of communication skills, the ability of senior workers to share knowledge with juniors, and provision of work motivation; and the expected results from competency improvement training basically include the ability to use a systematic method approach, combine work strategies, plans, settings, goals and priorities, and the ability to choose models of various types and styles of communication. The results showed that competency improvement training with achievement based on SKKNI had a close relationship, SKKNI influenced the improvement of the quality of human resources, but the training results were not significant for the human resources used by contractors.